KELAYAKAN JALUR EVAKUASI TSUNAMI DI KECEMATAN PADANG UTARA KOTA PADANG - Alexander Syam (STKIP Pesisir Selatan, 2016)
This study originated from the phenomenon of earthquakes that occurred in 2009 measuring 7.6 SR to swallow a lot of casualties. During the evacuation process is much buildup period because it is not like the evacuation route in the desert city. The purpose of this study was to analyze the spatial structure of North Padang related tsunami evacuation route and evaluate the feasibility of a tsunami evacuation route in the district of North Padang. This study was classified as a descriptive study using data from QuickBird Imagery interpretation in 2012 with the help of software ArcGIS 10.1, Quickbird image analysis to obtain administrative data, road networks, tsunami evacuation route, tsunami hazard zone through field surveys and analyzes BAPPEDA Kogami. Other supporting data obtained from the study of documentation and interviews related to research and population data from the BPS Padang. The results showed that (1) The structure of the existing space in the district of North Padang including the hazard of the tsunami, because there are many potholes and the condition of the road width of less than 10 meters. (2) evacuation path tsunami in North Padang still considered unfit as an evacuation route for tsunami evacuation on each line are point barrier which will cause congestion.